Adoption and implementation of a web-based self-management application “Oncokompas” in routine cancer care: a national pilot study - Matthijs de Wit, L. (Support Care Cancer, 2018)
PURPOSE: A web-based self-management application “Oncokompas” was developed to monitor health-related quality of life and to support cancer survivors in finding and obtaining optimal supportive care. Access to this application is provided via a healthcare professional (HCP). The aim of this study was to explore the adoption and implementation of Oncokompas in routine clinical practice and to obtain insights in potentially relevant determinants of implementation. METHODS: A pilot study was carried out among 65 hospitals throughout The Netherlands. HCPs filled out a questionnaire on the implementation of Oncokompas in their organization, consisting of study specific items and items based on the Measurement Instrument for Determinants of Innovations (MIDI). The MIDI comprises 29 determinants in four domains that predict the use of innovations: the innovation itself (Oncokompas), the user (HCP), the organization (hospital), and socio-political context. RESULTS: In total, 20/65 eligible hospitals agreed to implement Oncokompas (adoption rate 31%). In these 20 adopting hospitals, the majority of the responding HCPs (72/205) in this study (44/61) indicated their patients were offered access to Oncokompas (implementation rate 72%). Comparing those HCPs who did and did not implement Oncokompas, the groups differed significantly on innovation-related (procedural clarity, complexity) and user-related determinants (importance of outcome expectations, professional obligation, social support, and self-efficacy). CONCLUSIONS: During this 1-year study, nationwide adoption rate of Oncokompas was at 31%, and subsequent implementation rate was at 72%. The results of this study contribute to further optimize interventions and strategies to adopt and implement (online) self-management applications in cancer care. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00520-018-4591-5) contains supplementary material, which is available to authorized users.